Combined Mammographic and Sonographic Evaluation of Palpable Breast Mass - Badu, Muna; Simkhada, Rabindra (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Detection and evaluation of breast mass is challenging. Identification of malignancy in earliest possible stage is rewarding. Several radiological diagnostic modalities are available for this purpose including mammography and ultrasonography. The objective of the study was to evaluate the accuracy of mammography and ultrasonography individually and in combination to detect and characterize palpable breast mass and to correlate the imaging findings with histopathology. MATERIAL AND METHODS: Patients presented with palpable breast lump were examined prospectively. All patients were examined by both mammography and ultrasonography. Fine needle aspiration cytology was done for all findings. Correlations of mammography and ultrasonography findings were done with histopathology. RESULTS: A total of 42 patients were evaluated. Fine needle aspiration cytology revealed 30 (71.42%) benign and 12 (28.58%) malignant lesions. The sensitivity and specificity for mammography were 83.33% and 93.33% and for ultrasonography were 81.81% and 90.32% respectively. When findings of mammography and ultrasonography were combined, both sensitivity and specificity were increased to 91.66% and 96.66% respectively. CONCLUSION: Combined mammography and ultrasonography had higher sensitivity and specificity rate than sensitivity and specificity rate observed for either of single modality. This study suggests that any patient who is advised to go for a single modality of investigation should rather be investigated using the combined modality.